Fatty Acid Composition of Dairy Milk: A Case Study Comparing Once- and Twice-a-Day Milking of Pasture-Fed Cows at Different Stages of Lactation - Inthujaa Sanjayaranj; Nicolas Lopez-Villalobos; Hugh T. Blair; Patrick W. M. Janssen; Stephen E. Holroyd; Alastair K. H. MacGibbon (Dairy, 2022)
In this case study, we compared the gross composition and fatty acid (FA) composition of milk from cows milked once a day (OAD) and twice a day (TAD) at different stages of lactation in real farm conditions with no control on feed. Seventy-two cows from a OAD milking herd and 181 cows from a TAD milking herd were sampled in early, mid and late lactation. Calibration equations were developed to enable the prediction of proportions of individual FAs using mid-infrared (MIR) spectroscopy. Cows milked OAD produced 25% lower daily milk yield (MY) compared to cows milked TAD. Percentages of fat and protein were 21% and 9% higher in cows milked OAD compared to cows milked TAD, respectively. The proportion of saturated fatty acids (SFA) (molecules with unbranched hydrocarbon chains and all single bonds) was significantly lower, while the proportions of de novo synthesised FAs from C8:0 to C14:0 were significantly higher, in cows milked OAD compared to cows milked TAD. OAD milking improved the energy balance of cows, which led to higher proportions of de novo synthesised FAs and lower proportions of long-chain fatty acids (16:0 and above). The proportion of SFA was significantly higher in mid lactation (ML) compared to early lactation (EL) and late lactation (LL) in cows milked OAD and TAD. In EL, the proportions of C4:0 to C12:0 FAs in cows milked OAD were significantly higher compared to the cows milked TAD due to the improved energy status of cows milked OAD. Understanding the proportions of individual FAs in cows milked OAD and TAD will enable further studies on milk fat characteristics and on butter hardness and coagulation properties of milk.